Experimental Study of Split Grouting Reinforcement Mechanism in Filling Medium and Effect Evaluation - Jiandong Niu; Zewei Li; Weiheng Gu; Kang Chen (Sensors, 2020)
In view of the deficiency of the split grouting theory for the filling area, a 3D simulated grouting test system was designed to explore the slurry diffusion law, reinforcement mechanism of split grouting in a filling soil, and effect of grouting reinforcement. The test system included an experiment bench system, grouting system, and information monitoring system, using which experimental research on split grouting in a filling soil was conducted. The grouting model experiment procedure was introduced first, following which the diffusion rule of slurry in the filling medium and the reinforcement mechanism of split grouting were analyzed according to the properties and distribution characteristics of grouting veins after grouting reinforcement. Finally, a uniaxial compression test, light dynamic contact test, permeability test, and laboratory geotechnical test were conducted on the soil before and after grouting. The relationship between the zoning characteristics of different properties of veins and the mechanical properties of filling soil were discussed. The results showed that there were three types of grouting veins: trunk grouting, branch grouting, and permeable grouting. The injected soil body was strengthened by the three-stage grouting vein network of the mentioned vein types and the compaction between soils. After the grouting, the uniaxial compressive strength of the filling soil increased by an average of 186%, and the permeability coefficient decreased by an average of 47 times. The cohesion and internal friction angle increased by 45.3% and 44.9%, respectively. Additionally, density, water content, and other indicators of filling were improved. The bearing characteristics reflected by a dynamic contact test were consistent with the distribution of grouting veins. The research results offer significant guidance for the reinforcement mechanism of split grouting and the evaluation of the grouting effect.